Analysis of Tourism Preferences to Tourism Object in North Sumatera: Examining the Environmental Attachment - TEVIANA, T.; RUSLAN, Dede; SYAHREZA, Dina Sarah; SIREGAR, Zulkarnain (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021, 2021)
The purpose of writing this paper is to determine and analyze how tourist perceptions of the service quality of tourist areas, tourism attractiveness of tourist satisfaction with estuary. The objective of the research was to analyze the competitiveness of tourist destinations in the North Sumatra region as an effort to expand theoretical and empirical evidence about the structural relationships among constructs the impact of tourism development, environmental attitudes, place attachment, development preferences about destination attractions as the resources, and support for a comprehensive strategy to improve competitiveness objectives. To identify and analyze the development of competitiveness of North Sumatra tourism based on visitor perspectives that reflect the services expected by the demand side, the method of data collection and data analysis used in the research on is the quantitative method of Structural Equation Modeling (SEM). Based on the results of research and analysis of the tourist preference indicators of tourist objects in North Sumatra, it was found that in empowering tourist areas with the development of the image of tourist areas in North Sumatra Province, it is necessary to prioritize the development of elements of tourism image builders that contribute greatly, namely human resource development, security and safety, hygiene and health, preferences and prices, and marketing strategies. In addition, to increase the competitiveness of tourist areas, a business climate policy and sustainability of protection, facilities and infrastructure are needed as well as increased tourist attraction.